Industrial Relations with Specific Time Work Agreements after the Decision of the Constitutional Court of the Republic of Indonesia Number 91/PUU-XVIII/2020 in The Perspective of Legal Justice - Fithriatus Shalihah (Jurnal Hukum Novelty, 2022)
Introduction to The Problem: The constitutional court decision No. 91/PUU-XVIII/2020 stated that the establishment of Law No. 11 of 2020 on Job Creation contradicts the 1945 Constitution and is considered conditional unconstitutional. Thus, within two years of Law No. 11 of 2020, its derivative rules are still enforced until there is an improvement. However, two years is a legal certainty, but it is uncertain in the business and industrial worlds.Purpose/Objective Study: This study aims to find out how the effect of the issuance of the Constitutional Court of the Republic of Indonesia No. 91/PUU-XVIII/2020 on the implementation of Law No. 11 of 2020 on the Employment Cluster and its derivative rules and how alternative efforts in creating harmonious industrial relations on the issue of working relations with Specific Time Work Agreements after the constitutional court decision No. 91/PUU-XVIII/2020.Design/Methodology/Approach: The research method used is doctrinal legal research.Findings: This research resulted in a study that the influence of constitutional court decision No. 91/PUU-XVIII/2020 impacts the uncertainty of legal protection guarantees in the business and the industrial world. Because it takes two years to implement the provisions of Law No. 11 of 2020 in the Employment cluster and its derivative rules, namely Government Regulation No. 35 of 2021, the business and the industrial world cannot implement the provisions without any guarantee of sustainable time, and it will lead to injustice in industrial relations. One alternative to continue creating harmonious industrial relations with Specific Time Work Agreements is to return to local wisdom, prioritizing the principle of consensus deliberation that prioritizes the parties' agreement in working relations including the fulfillment of rights in compensation payments when there is a termination of employment.Paper Type: Research Article